DON IZ HAR ONDT I MAVEN: Delt social erfaring og sameksisterende refleksiviteter - Hervik, Peter (Tidsskriftet Antropologi, 1995)
Peter Hervik: Don Iz’ Stomach Aches. Shared Social Experience and Co- Existing Reflexivities This article delimits a locus of study centered on the notion of shared social experience which draws on the author’s fieldwork among the Mayas of Yucatan in Mexico. Shared social experience concems the conscious identity of the ethnographer, the nature of relationships with local informants, and his or her willingness to be enganged in the lived experince of native actors. Only if we engage ourselves direetly in the practical and emotional concems of others in the field can we demystify subjectivity and gain insight into other reflexivities and reflexivities in their interactional mode.